L’Acacia de Claude Simon: L’écriture à l’épreuve du tragique - Maria de Jesus Cabral (Carnets)
How is the violence of life staged, before the entangled threads of memory, the “black corpse of History”? Published in 1989, four years after being awarded the Nobel Prize, Claude Simon’s Acacia transposes the tragic journey of a family through dissolution of references – personal, time and space – to find the cracks in the narrative that trace a destiny which no simple novelistic form is able to represent. The page becomes a place that questions the limits of the novel and the limits of language by engraving a text out of a new bark where the tragic merges with the story.